2019
DOI: 10.1515/opphil-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

New Public Monuments: Urban Art and Everyday Aesthetic Experience

Abstract: The role and function of public art is currently undergoing some large-scale changes. Many new artworks which are situated within the already existing urban sphere, seem to be changing the definition of public art, each in their own way. Simultaneously, there exists a trend that endorses more traditional forms of public art. Juxtaposing and comparing the aesthetic implications of different types of artworks, it is possible to see how they contribute to the contemporary understanding of the urban sphere. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Scholarly thought about public art has made large strides, moving beyond traditional art, historical, "formalist" methods that focus on the style of artworks found in typical art exhibition contexts of museums and gallery spaces (e.g., Phillips 1988; Senie and Webster 1992;Hein 2006;Knight and Senie 2018). Along with a mounting presence of art in public community spaces of democratic societies (see Doss 1995;Deutsche 1996), research into public art has evolved in a multidisciplinary fashion, involving case studies that emphasize the wide gamut, and on-going reconfiguration, of relationships between art, public space, audiences, encounters, and participation (e.g., Zebracki 2012;Warren 2013;Vernet 2015;Gurney 2018;Lehtinen 2019). This widening scope of public art has offered rich study material for scholars across the (geo)humanities and social sciences to reflect on the complexity of the social and spatial dimensions and impacts of public art practices and engagement (e.g., Finkelpearl 2001;Kwon 2004;Knight 2008;Bishop 2012;Cartiere and Zebracki 2016;Radice and Boudreault-Fournier 2017).…”
mentioning
confidence: 99%
“…Scholarly thought about public art has made large strides, moving beyond traditional art, historical, "formalist" methods that focus on the style of artworks found in typical art exhibition contexts of museums and gallery spaces (e.g., Phillips 1988; Senie and Webster 1992;Hein 2006;Knight and Senie 2018). Along with a mounting presence of art in public community spaces of democratic societies (see Doss 1995;Deutsche 1996), research into public art has evolved in a multidisciplinary fashion, involving case studies that emphasize the wide gamut, and on-going reconfiguration, of relationships between art, public space, audiences, encounters, and participation (e.g., Zebracki 2012;Warren 2013;Vernet 2015;Gurney 2018;Lehtinen 2019). This widening scope of public art has offered rich study material for scholars across the (geo)humanities and social sciences to reflect on the complexity of the social and spatial dimensions and impacts of public art practices and engagement (e.g., Finkelpearl 2001;Kwon 2004;Knight 2008;Bishop 2012;Cartiere and Zebracki 2016;Radice and Boudreault-Fournier 2017).…”
mentioning
confidence: 99%
“…As for the experience of designing Urban Scenes, a (Drama of the Unexpectedness) emerged when natural scenes suddenly unfold while walking around the buildings, stimulating the pleasure of the passersby through visual contrasts or/and changing levels in order to generate a shock or surprise (Gassner, 2013). In fact, what gives the experience of the unknown in the urban environment its attributes, is the element of surprise and pleasure, as well as the shocking diversity that depends on many factors (Lehtinen, 2015). Previous studies indicated that Surprise is one of the built environment affective qualities that resulted from linking the affective responses to the specified physical characteristics of the built environment which work as stimuli.…”
Section: Surprise As a Phenomenon For Detection Using 3d Isovistmentioning
confidence: 99%
“…Rezafar ve Türk (2018) çalışmalarında, mimari estetiğin sadece yapıların fiziksel özellikleri ile ilgili olduğunu, kent estetiğinin ise kentsel ölçekte daha geniş değerlerle ortaya çıktığını söylemektedirler. Lehtinen (2019) çalışmasında, kentsel estetiğin çevresel estetikten geldiğini, ayrıca köklerinin mimari teoride olduğunu dile getirmektedir. Konuyla ilgili olarak Ghomeshi ve Jusan (2013) çalışmalarında, çevresel estetiğin duyularımıza nasıl zevk verebileceğine odaklandığını belirtmektedirler.…”
Section: Introductionunclassified
“…Rezafar and Türk (2018) state that architectural aesthetics is only related to the physical properties of buildings, and that urban aesthetics is more widespread in urban scale. In his study, Lehtinen (2019) states that urban aesthetics comes from environmental aesthetics and that its roots are in architectural theory. On the subject, Ghomeshi and Jusan (2013) state that environmental aesthetics focuses on how to give pleasure to our senses.…”
Section: Introductionmentioning
confidence: 99%